Parenting Patterns in Overcoming Reading Difficulties in Grade V Students at Public Elementary School Gondangslamet 2 Boyolali - Ryanto, Aldora Zahra; Sutama, S (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2023)
This article discusses parenting and innovative learning approaches in overcoming reading difficulties in grade V students at Gondangslamet 2 Boyolali State Elementary School. Parenting is necessary to support learning success. The purpose of this study is 1) To describe the extent to which parenting overcomes reading difficulties of fifth-grade children at Gondangslamet 2 Boyolali State Elementary School; 2) to explore the effectiveness of innovative learning approaches in improving the reading skills of fifth-grade children at the school. The research method is qualitative with a phenomenological approach. The research subjects involved parents and grade V students at Gondangslamet 2 Boyolali State Elementary School. Data were collected by interview and documentation analysis. Data validity using triangulation of sources and methods. The results showed, that 1) Actively involving parents in supporting children's reading skills, both at home and at school; 2) Applying innovative learning approaches can be an effective strategy in overcoming reading difficulties in grade V children.